PENGEMBANGAN CHATBOT TELEGRAM FAQ LAYANAN ICT MENGGUNAKAN ALGORITMA RANDOM FOREST DAN METODE WORD2VEC (INTI Nusa Mandiri, 2025)
In today's digital era, chatbots have become an essential tool for businesses to improve interaction with customers. A responsive and efficient chatbot can help customer service agents be happier, improve customer satisfaction, and resolve issues faster. The study aims to create a  Telegram-based chatbot that uses  the Random Forest algorithm  and the Word2Vec method  to answer questions about ICT services. The development was carried out by collecting a dataset of  questions and answers from FAQs (Frequently Asked Questions) of ICT services. Then,  the Random Forest algorithm  is used to classify the questions. In addition, the Word2Vec method  is used to create vector representations of words in questions and answers. This improves  the chatbot's ability  to understand complex questions. The test results show that  the chatbot gets an accuracy of 91.28%, a precision of 93.56%, a recall of 91.28% and  an F1-Score of 91.42% and can provide relevant and accurate answers to user questions. Therefore, the development of  this chatbot using  the Random Forest algorithm  and the Word2Vec method can be an effective solution to improve customer service in the field of ICT services
Keywords: Chatbots; ICT Services; Random Forest Algorithms; Word2Vec